Fiscal consequences of corporate tax avoidance - Katarzyna Bilicka; Evgeniya Dubinina; Petr Janský (Charles University in Prague, Institute of Economic Studies (IES), 2023)
We study the consequences of multinational tax avoidance on the structure of government tax revenues. To motivate our analysis, we show that countries with high revenue losses due to profit shifting have lower corporate tax revenues and rates and higher indirect tax revenues and rates. To establish causality, we use German municipal data and analyse how changes in municipal trade tax rates levied on corporate profits affect local tax revenue structure. Following a trade tax rate increase, we find that municipalities with high exposure to aggressive multinationals experience a significant decline in trade tax revenue levels and shares.
Keywords: E62; H26; H71; 330; Corporate Tax Avoidance; Profit Shifting; Multinational Corporations; Government Tax Revenue Structure